Penguatan Pendidikan Karakter dalam Pembelajaran Matematika - Rusminati, Susi Hermin; Apri Irianto; Arif Mahya Fanny (Universitas PGRI Adi Buana Surabaya, 2021)
Penguatan Pendidikan Karakter which was later abbreviated to PPK. PPK is the implementation of President Joko Widodo's program through Presidential Decree No. 87 of 2017 on Penguatan Pendidikan Karakter. This PPK policy was then integrated with the Gerakan Nasional Revolusi Mental or abbreviated as GNRM. The values instilled in this PPK are Religious, Nationalist, Independent, Mutual Cooperation and Integrity. Penguatan Pendidikan Karakter (PPK) consisting of religious, nationalist, independent character, Mutual Cooperation and integrity can be implemented in the course of the lesson. By linking PPK in mathematics lessons later it is expected to shape the character of learners to be better through mathematical concepts.